An interactive, multi-modal Anatomy workshop improves academic performance in the health sciences: a cohort study. Issue 1 (December 2016) - Nicholson, Leslie; Reed, Darren; Chan, Cliffton
Abstract Background Students often strategically adopt surface approaches to learning anatomy in order to pass this necessarily content-heavy subject. The consequence of this approach, without understanding and contextualisation, limits transfer of anatomical knowledge to clinical applications. Encouraging deep approaches to learning is challenging in the current environment of lectures and laboratory-based practica. A novel interactive anatomy workshop was proposed in an attempt to address this issue. Methods This workshop comprised of body painting, clay modelling, white-boarding and quizzes, and was undertaken by 66 health science students utilising their preferred learning styles. Performance was measured prior to the workshop at the mid-semester examination and after the workshop at the end-semester examination. Differences between mid- and end-semester performances were calculated and compared between workshop attendees and non-attendees. Baseline, post-workshop and follow-up surveys were administered to identify learning styles, goals for attendance, useful aspects of the workshop and self-confidence ratings. Results Workshop attendees significantly improved their performance compared to non-attendees (p = 0.001) despite a difference at baseline (p = 0.05). Increased self-confidence was reported by the attendees (p < 0.001). To optimise their learning, 97 % of attendees reported utilising multi-modal learning styles. Five main goals for participating in the workshop included: understanding, strategic engagement, examination preparation, memorisation and increasing self-confidence. All attendees reported achieving these goals. The most useful components of the workshop were body painting and clay modelling. Conclusions This interactive workshop improved attendees' examination performance and promoted engaged-enquiry and deeper learning. This tool accommodates varied learning styles and improves self-confidence, which may be a valuable supplement to traditional anatomy teaching.